A mechanically strengthened polyacrylamide gel matrix fully compatible with electrophoresis of proteins and nucleic acids. Issue 5 (11th December 2017) - Pushparajan, Charlotte; Goswami, Shailesh K.; McAdam, C. John; Hanton, Lyall R.; Dearden, Peter K.; Moratti, Stephen C.; Cridge, Andrew G.
Abstract: Polyacrylamide gel electrophoresis is a universal tool in a biochemist's toolkit for protein and nucleic acid separation and subsequent visualisation and analysis. The standard formulation of polyacrylamide gels consists of acrylamide (ACM) monomer crosslinked with bisacrylamide (MBA) which creates a gel with excellent sieving properties but which is mechanically fragile and prone to tearing during post‐electrophoresis manipulations involved in visualisation and analysis. By adding a poly(ethylene oxide) macro‐crosslinker to the standard gel formulation, we have created a tough gel matrix that can be used to fractionate proteins and nucleic acids by polyacrylamide gel electrophoresis. The protein and nucleic acid resolving capabilities and performance during staining and electroblotting of the tough gel matrix rivals that of conventional acrylamide/bisacrylamide gels. The tough gel matrix is resistant to tear and remarkably elastic, capable of stretching to over four times its original length before breaking, and represents a significant improvement over standard polyacrylamide gel formulations.